LncRNA-GAS5 Inhibits Expression of miR 103 and Ameliorates the Articular Cartilage in Adjuvant-Induced Arthritis in Obese Mice - Hongwei Chen; Chuan He; Yan Liu; Xiaolin Li; Chaoju Zhang; Qunyan Qin; Qixiong Pang (SAGE Publishing, 2020)
We explored whether long noncoding RNA growth arrest-specific transcript 5 (LncRNA-GAS5) small interfering RNA (siRNA) reduced cartilage destruction in obese mice with adjuvant-induced arthritis. We studied the effects of LncRNA-GAS5 siRNA on the polyarthritis index; hind paw swelling; and the serum levels of certain biochemicals, cytokines, and oxidative stress parameters. We measured the expression levels of matrix metalloproteinases (MMP)-13, NF-κB, fibroblast growth factor (FGF) 21, p38, Akt, and PI3K in cartilage via Western blotting and quantitative reverse transcription PCR. Long noncoding RNA-GAS5 siRNA reduced joint swelling; the serum levels of arthritis-associated biochemicals, cytokines, and oxidative stress markers; and cartilage MMP-13, NF-κB, FGF21, p38, Akt, and PI3K levels. Cartilage miR-103 expression was reduced. Histopathologically, LncRNA-GAS5 siRNA ameliorated the pathological changes of cartilage. Long noncoding RNA-GAS5 siRNA prevented cartilage destruction by inhibiting miR-103 expression.